Expression of circulating CD146 associated with endovascular dysfunction in adenine-induced chronic renal damage in rats using an EvaGreen real-time RT-PCR assay - P., Farah Dina; Hamzah, Hazilawati; Shaari, Mohd Rosly; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2011)
The integrity of the endothelial layer of the blood vessel, intima, is critical since damage can lead to atherosclerosis. Assessment of its integrity is therefore very important although this can not be done through routine diagnostic analysis. An alternative non-invasive method should be established to assess its integrity. The objective of this study was to develop a quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR) using an EvaGreen dye for the assessment of vascular endothelial damage-associated with chronic renal damage in rats via quantification of the expression level of CD146, which is one of the blood biomarkers of endovascular dysfunction and/or damage. Comparison of the sensitivity of the EvaGreen qRT-PCR and the conventional RT-PCR was also performed in this study. For this purpose, a total of 16 male Sprague Dawley rats were divided equally into two groups, namely the control and adenine. Results showed that rats fed with diet containing 0.75% adenine for six consecutive weeks developed chronic renal damage through elevations in the blood urea nitrogen (BUN) and blood creatinine (Cr) levels, increased urine protein to creatinine ratio (UPC) and decreased creatinine clearance (CrCl). The confirmatory diagnosis of chronic renal damage was made through gross and histopathological examinations of the kidneys. The results were consistent with lesions of chronic renal damage. The expression of circulating CD146 was mildly increased in rats with chronic renal damage analysed using the EvaGreen qRT-PCR or the conventional RT-PCR, suggesting a mild degree of endovascular damage. The intensity of the EvaGreen qRT-PCR products, however, was brighter than the conventional RT-PCR, indicating that the EvaGreen qRT-PCR is more sensitive compared to conventional RT-PCR, which is further recommended for analysis of CD146 expression in rats.